Effect of the application Intervention and management pharmaceutical “Carica papaya”, to help reduce some symptoms gastroesophageal - Junchaya Yllescas, Vilma Amparo (2020)
The frequent heartburn after meals is common in people who suffer from some gastro symptoms, and if not addressed can cause problems ranging from bleeding, to an inﬂammation and ulceration. In Peru these symptoms are common in early ages of life, and there is no difference between the populations of the Costa, Sierra and jungle forest of  Peru, therefore this research was conducted in order to determine the effect of the application Intervention and management pharmaceutical “Carica papaya”, to help reduce some symptoms gastro esophageal; performed in doctor's ofﬁce and research lab in 30 students UPH purposive sample of the CEPRE, quasi-experimental design, divided into two groups. Where the experimental group received 500 ml of unripe Carica papaya juice for 30 days, associated with pharmaceutical intervention based on the use of some chips as pharmaceutical recommendation, nonlinguistic code and visual and written dosage, concluding that the regurgitation, difﬁculty swallowing and belching as gastro esophageal symptoms decreased markedly unlike that in the control group did not change signiﬁcantly.